Zastosowanie metod aglomeracyjnych w analizie przestrzenno-czasowej modelowania bezrobocia rejestrowanego w Polsce - Rozpędowska-Matraszek, Danuta (Application of Clustering Methods in Space-Time Modeling of Labour Unemployment in Poland, 2007)
In this paper, there are presented the results of the spatiotemporal analysis concerning unemployment rates in Poland. The empirical research refers to the unemployment labour, education market end unemployment state in some period of time, for Polish voivodships. Quarterly data were used in these analysis (from IV quarter 1996 to I quarter 2006) clustering metod was implemented to point out the most similar voivodships in Poland. Using panel date to estimate allowed both using the inflection about time and specification of observed objects.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 279-287